PENGEMBANGAN DESAIN STARTING BLOCK KOLAM RENANG DENGAN MENGGUNAKAN THEORY OF INVENTIVE PROBLEM SOLVING (TRIZ) - Denny Nurkertamanda; Asen Ahman (Diponegoro University, 2010)
Swimmingpool starting block is one of swimming equiptment that must be used in swimming sport competition.It used not only by senior athlete but also the beginner. In addition, it used not only in one swimmingpool butalso another pool which has different height of watersurface and swimmingpoll wallside.Now, the condition of starting block only fit with some of athlete. The other athlete had difficulties when use it.Because of that, design improvement need to be done for starting block to be adaptable for all athlete in anyage and adaptable for the condition of watersurface.Adaptability fitur improvement for starting block makes fitur stabilition of product composition getting worse,and those things is unwanted. So that Theory of Inventive Problem Solving (TRIZ) method is needed to solvethe problem technical contradiction so the ideal final output can be reached.Adaptable starting block design can be reached after solve the technical contradiction happened when solvingthe problems used TRIZ. Reducing the parameters which had disadvantages for the ideal final product suchas: weight of the moving object, quantity of the material used, dangerous factor of the object, and dangerousfactors from environtment.